The Provision of Residential Park as a Green Open Space to Accommodate the Children's Activity (Case Study: Bentiring Permai II Residence, Bengkulu City) - Renitha Sari; Juwito, Rizqiyah Safitri; Pratimi, Mariska (MultiTech Publisher, 2024)
The residential playpark is very important, as it is the best alternative place for children to move freely, get to know the environment and socialize. But in reality, there are still many residences that are not equipped with a proper park facility or have no a park at all. One of them is Bentiring Permai II Residence. Based on these problems, this research is conducted to find out how important the existence of playparks and the minimum park design and facilities for children's activities according to their age. This research type is a qualitative descriptive. The result will be a direction for the park layout to suit the residential area conditions and provide the activities for all ages of children.